DIGITAL COMPETENCE AND INNOVATIVE PEDAGOGY IN MODERN EDUCATION: CHALLENGES AND PROSPECTS (American Journal of Pedagogical and Educational Research, 2026)
The rapid digital transformation of society has significantly influenced the structure and content of modern education systems. Educational institutions worldwide are increasingly integrating digital technologies, online platforms, and innovative teaching methods into the learning process. In this context, the development of digital competence among teachers and students has become a key factor in ensuring the quality and effectiveness of education.This article explores the role of digital competence and innovative pedagogicalapproaches in modern education. The study analyzes theoretical foundations of digital pedagogy, identifies the main components of digital competence, and examines their importance in improving teaching and learning processes. Particular attention is given to the transformation of the teacher's role in the digital educational environment and the implementation of innovative instructional strategies.